2023
DOI: 10.3390/ijms241713135
|View full text |Cite
|
Sign up to set email alerts
|

Octacalcium Phosphate-Laden Hydrogels on 3D-Printed Titanium Biomaterials Improve Corrosion Resistance in Simulated Biological Media

Aydin Bordbar-Khiabani,
Ilijana Kovrlija,
Janis Locs
et al.

Abstract: The inflammatory-associated corrosion of metallic dental and orthopedic implants causes significant complications, which may result in the implant’s failure. The corrosion resistance can be improved with coatings and surface treatments, but at the same time, it might affect the ability of metallic implants to undergo proper osteointegration. In this work, alginate hydrogels with and without octacalcium phosphate (OCP) were made on 3D-printed (patterned) titanium alloys (Ti Group 2 and Ti-Al-V Group 23) to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…According to the diameter of the capacitive loops in Nyquist plots ( Fig. 3 c), the PEO/PEG-BET-coated Ti had a larger loop radius than PEO, indicating high protection efficiency in both media [ 2 , 3 ]. The Bode modulus plots are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the diameter of the capacitive loops in Nyquist plots ( Fig. 3 c), the PEO/PEG-BET-coated Ti had a larger loop radius than PEO, indicating high protection efficiency in both media [ 2 , 3 ]. The Bode modulus plots are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation triggered after implantation can lead to the release of hypochlorous acid (HOCl) by osteoclasts and white blood cells, creating a local acidic pH region (pH ~ 5) around the implant. Consequently, surface treatment processes are essential to enhance the corrosion resistance of titanium implants in acidic inflammatory environments [ 3 ]. Long-term alleviation of inflammation may be achieved through the systemic delivery of anti-inflammatory drugs on the Ti surface.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, hydrogel loaded with a VEGF-mimetic peptide (QK) demonstrated the ability to enhance tube formation in human umbilical vein endothelial cells (HUVECs), elevate the expression of angiogenesis-related genes (Flt1, Kdr and VEGF) in BMSCs (Figure 3f) and recruit BMSCs, collectively contributing to the establishment of an osteogenic microenvironment for bone repair [81]. Bordbar-Khiabani et al explored 3D-printed titanium alloys that were covered with alginate hydrogels with and without OCP to improve their resistance to corrosion under simulated normal, inflammatory and severe inflammatory conditions in vitro [82]. The findings indicated that alginate hydrogel/OCP coatings exhibited higher hydrophilicity compared to that of pure alginate hydrogel.…”
Section: Octacalcium Phosphate (Ocp) As Biomaterialsmentioning
confidence: 99%
“…Additionally, the corrosion resistance is significantly reduced when lactic acid and H 2 O 2 are present [53]. Further research has demonstrated that hydrogel coatings can serve as a barrier, preventing chloride and lactate ions in simulated biological environments from causing corrosion to the underlying material, thus enhancing the Ti alloy's resistance to corrosion [54].…”
Section: Dynamic Responsive Surfacesmentioning
confidence: 99%